Anterior Segment Optical Coherence Tomography for Targeted Transconjunctival Suture Placement in Overfiltering Trabeculectomy Blebs. Issue 5 (May 2017) - Heisler, Morgan; Quong, Whitney L.; Lee, Sieun; Han, Sherry; Beg, Mirza F.; Sarunic, Marinko V.; Mackenzie, Paul J.
Abstract : Purpose: To demonstrate the utility of swept-source anterior segment optical coherence tomography (SS-AS-OCT) in guiding placement of transconjunctival sutures in hypotonous patients after a trabeculectomy. Patients and Methods: This is a longitudinal case series of 10 eyes from 10 patients who required transconjunctival sutures after a trabeculectomy. SS-AS-OCT was used to aid in the placement of the sutures to improve the function of the overfiltering bleb. Results: SS-AS-OCT reliably identified localized areas of overfiltering, allowing for targeted suture placement in 8 eyes. The 2 eyes in which localized areas of overfiltering were not found required further surgical intervention. Conclusions: SS-AS-OCT enhances transconjunctival suturing for overfiltering blebs when focal fluid accumulation is visualized.